1999
DOI: 10.1088/0266-5611/15/2/018
|View full text |Cite
|
Sign up to set email alerts
|

Positive solutions to linear inverse problems

Abstract: We discuss two methods for incorporating the prior knowledge that the solution is positive into the truncated singular value decomposition method for solving linear inverse problems. The methods are based on mathematical programming techniques. One method can be viewed as a primal method and the other as its dual. Provided the singular functions are analytic these methods both deliver the same solution-namely the positive solution of minimum 2-norm which agrees with the truncated singular function expansion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…We use this flexibility of choosing the expansion coefficients to produce a solution satisfying constraints (9.55) [78]. The relative advantages of each method will be discussed elsewhere [79].…”
Section: -Response To External Probes and The Spectral Functionmentioning
confidence: 99%
“…We use this flexibility of choosing the expansion coefficients to produce a solution satisfying constraints (9.55) [78]. The relative advantages of each method will be discussed elsewhere [79].…”
Section: -Response To External Probes and The Spectral Functionmentioning
confidence: 99%
“…Taking into account that for an ill-posed problem such as (8) the singular values σ j vanish overexponentially with increasing j it becomes obvious that only the first few terms in the expansion (12) contain meaningful information whereas the higher terms will just corrupt the result by amplifying the noise of the data. This idea is used in the truncated SVD approach 19,20 which truncates the summation in (12) by neglecting all terms for which σ j /σ 0 is smaller than the statistical error of the correlation function C(τ ).…”
Section: B Analytic Continuationmentioning
confidence: 99%
“…Previous studies 19,21 have shown that this implementation of positiveness reduces the resolution of the method. Recent work 20 has shown how to use supplementary information of positiveness to enhance the resolution of the singular value decomposition method. The idea is to determine additional expansion coefficients which cannot be inferred from the inverse problem.…”
Section: B Analytic Continuationmentioning
confidence: 99%
“…(30) can be different from the set I of Eq. (18). The former is actually the result of an algorithm acting on a given set of data and can be thought of as a numerical realization of the theoretical set I of (18).…”
Section: B Statistical Analysis Of the Noisy Datamentioning
confidence: 99%
“…(18). The former is actually the result of an algorithm acting on a given set of data and can be thought of as a numerical realization of the theoretical set I of (18). A similar role is played by the numerical approximation f I (x) with respect to the theoretical approximation Bḡ of Eq.…”
Section: B Statistical Analysis Of the Noisy Datamentioning
confidence: 99%